Transformasi Pemolisian Demokratis di Papua - Hery Herjawan; Djuni Thamrin (Jurnal Kajian Ilmiah, 2023)
The aim of this research is to see the potential of optimizing the democratic policing approach in Papua in creating Papuan security stability that is inclusive, based on community involvement, and involved in fulfilling social demands. The research method used in this research is a qualitative research method using interview data collection techniques. In the implementation of conflict policing in Papua, it can be a simulacra in transforming the style/model of policing to be more democratic which produces outputs in overcoming conflict in Papua. The democratic policing that is expected to be achieved in Papua also indicates fundamental changes in policing styles that require intervention at the macro, meso and micro levels in the implementation of policing in the context of conflict management in Papua.